Vitellogenins Level as a Biomarker of the Honeybee Colony Strength in Urban and Rural Conditions - Łukasz Nicewicz; Agata Wanda Nicewicz; Mirosław Nakonieczny (Insects, 2024)
The study aimed to verify whether urban beekeeping affects the strength of the honeybee (Apis mellifera) colonies from urban apiaries and the variability of the crucial for their health and long-life protein—vitellogenins. For this purpose, honeybees were kept in two locations—in a city apiary on a roof in the city center and in agricultural areas. Each of the apiaries consisted of six colonies, with the sister queens artificially inseminated with semen from the same pool of drones. The bee colony strength and the variability of the vitellogenins in various tissues in foragers from both apiaries were analyzed from May to August. Here, we revealed that colonies from the urban apiary were more abundant than those from the rural apiary. We observed the compensation mechanism during periods of worker deficiency in the bee colony, which was expressed as a change in the Vgs level in the forager tissues. Using the vitellogenin level as a biomarker of the honeybee colony strength can predict the fate of colonies, especially those with low numbers. The high level of Vgs can be a candidate for bee colony depopulation biomarker.